(untitled) (Palíndromo, 2021)
Recognizing the importance of Tributo as a creation space where pedagogical and digital processes are linked, allows the Fashion Design program of the Corporación Unificada Nacional de Educación Superior CUN in Bogota to move from a personal experience to virtual teaching, as a result of the context variables, to guide the creation processes of the students that are consolidated from the distant viewpoint of the professor. Three fundamental elements are identified to articulate the research process: the otherness to understand the strategies from the virtual education; the possibility of diversifying the products from the digital creation and the use of didactic tools, where it gamifies to harness the levels of motivation of the students; the pedagogic and creative practice from the sustainability. We find that teachers establish strategies to take the training of university students through a motivating route that is evidenced in the diversity of products that goes beyond the conventional costume format and focuses on the iconic message, photography, editing, visual and musical remix, which enhance other skills that fashion students in the search for a comprehensive, competitive, sensitive and creative professional.